Mcardle’s Disease Complicated by Acute Renal Failure - Muhammad Sarfraz, Sehrish Iqbal, Abdul Kabeer Baig, Muhammad Khurram, Zaina Sajid, Faramarz Khan, Madeeha Nazar, Nida Anjum, Salman Mushtaq, (Pakistan Journal of Medical & Health Sciences, 2022)
McArdle’s disease is a Glycogen storage disease (type V) which is caused due to the inherited deficiency of myophosphorylase enzyme required for the breakdown of muscle glycogen. It typically presents with complaints of exercise intolerance, early fatigability, and muscle aches. The disease can be complicated by rhabdomyolysis in severe cases. We present the case of a 27 years old male with McArdleʼs disease who presented with bilateral lower limbs weakness associated with muscle aches and dark colored urine which later turned into anuria. Diagnosis of acute renal failure complicating rhabdomyolysis in background of McArdle’s disease was made.